2017
DOI: 10.1016/j.gmit.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal vault drainage after complicated single-port access laparoscopic-assisted vaginal hysterectomy

Abstract: Study objective:To evaluate the feasibility and safety of vaginal vault drainage after complicated singleport access laparoscopic-assisted vaginal hysterectomy (SPA-LAVH).Design:Retrospective cohort study.Setting:Ulsan University Hospital (tertiary teaching hospital), South Korea.Patients:A total of 359 women underwent SPA-LAVH for the following conditions: benign uterine tumor, preinvasive uterine lesion, and microinvasive cervical cancer.Interventions:The participants included 124 women with vault drains and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Another retrospective study evaluated the efficacy and safety of vaginal vault drainage after a complicated single-port access laparoscopic-assisted vaginal hysterectomy. Although there was a tendency for patients with vaginal drainage to develop pelvic fluid collection and febrile morbidity occurred more frequently than that in patients without drainage, the differences were minimal regarding transfusion rates, intraoperative and perioperative complications, and febrile morbidity [ 10 ]. In contrast, a retrospective study found that leaving a patent tract in the vaginal vault instead of a complete closure significantly reduced the possibility of pelvic hematoma infection after a vaginal hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective study evaluated the efficacy and safety of vaginal vault drainage after a complicated single-port access laparoscopic-assisted vaginal hysterectomy. Although there was a tendency for patients with vaginal drainage to develop pelvic fluid collection and febrile morbidity occurred more frequently than that in patients without drainage, the differences were minimal regarding transfusion rates, intraoperative and perioperative complications, and febrile morbidity [ 10 ]. In contrast, a retrospective study found that leaving a patent tract in the vaginal vault instead of a complete closure significantly reduced the possibility of pelvic hematoma infection after a vaginal hysterectomy.…”
Section: Discussionmentioning
confidence: 99%